PHYSICS TEACHING MATERIALS WITH ETHNO, INQUIRY, AND PROJECT APPROACHES TO IMPROVE MULTIPLE SKILLS OF PROSPECTIVE EDUCATORS - Muhammad Jhoni; Sofyan Sofyan; Jumhur Jumhur; Winarto Winarto (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
This study explores the effectiveness of integrating Ethno-Inquiry-Project approaches into physics education to enhance the multiple skills of prospective physics educators. The primary objective is to develop teaching materials that connect physics concepts with local cultural contexts to improve critical thinking, problem-solving, communication, and collaboration skills. Utilizing a Research and Development (R&D) methodology based on the 4D model (Define, Design, Develop, Disseminate), the study involved 40 third-semester physics education students at UIN Raden Fatah Palembang. The development process included literature review, preliminary studies, expert validation, and field trials. Validation results indicated high feasibility, with significant improvements in students' skills: critical thinking (30%), problem-solving (36.67%), collaboration (25.71%), and communication (26.47%). Observations confirmed active student engagement and effective group collaboration. The findings demonstrate that the EIP approach not only deepens understanding of physics concepts but also integrates cultural relevance, making learning more engaging and applicable. These results suggest broad implications for enhancing physics education by incorporating local contexts, thus providing a holistic learning experience that prepares future educators for 21st-century challenges. Further research is recommended to generalize findings across diverse educational settings and explore long-term impacts. This study underscores the potential of EIP-based teaching materials to significantly improve the quality of physics education and the skill sets of future educators.